Pregnancy outcome in women with gestational diabetes mellitus according to the Carpenter–Coustan criteria in Thailand. Issue 9 (26th June 2015) - Luengmettakul, Jiraporn; Sunsaneevithayakul, Prasert; Talungchit, Pattarawalai
Abstract: Aim: To compare the pregnancy outcome of patients diagnosed with gestational diabetes mellitus (GDM) using the Carpenter–Coustan (CC) criteria with that of non‐GDM pregnant women at Siriraj Hospital, Bangkok. Methods: A retrospective study was carried out by reviewing medical records of pregnant women who underwent 100‐g oral glucose tolerance test (OGTT) for diagnosing GDM between January 2009 and December 2012 at Siriraj Hospital. Pregnant women were divided into three groups according to the 100‐g OGTT result: group 1, pregnant women with normal OGTT on both CC and National Diabetes Data Group (NDDG) criteria; group 2, pregnant women with normal OGTT on NDDG criteria but GDM on CC criteria; and group 3, pregnant women with GDM on CC criteria after December 2012 and enrolled in glycemic control program. Maternal and perinatal outcomes were compared between the groups. Results: During the study period, the incidence of GDM increased 32.76% using the CC criteria. These women (group 2) had a higher risk of neonatal hypoglycemia (6.7% vs 0.6%; OR, 12.3; P < 0.0001), neonatal hyperbilirubinemia (13.7% vs 7.8%; OR, 1.9; P = 0.013) compared with group 1. Pregnant women in group 3 had a lower incidence of immediate post‐partum hemorrhage from vaginal delivery than group 2 (0 vs 2.9%; P = 0.04) as well as lower rates of neonatal hypoglycemia and neonatal hyperbilirubinemia. Conclusion: Use of CC criteria increases the prevalence of GDM, but managing these women according to the program for GDM can improve the adverse neonatal outcome.